White adipose tissue browning and peroxisome proliferator activated receptors in MASLD - Li, Zexuan; Chu, Huikuan; Yang, Ling (Frontiers in Endocrinology, 2025)
Metabolic dysfunction associated steatotic liver disease (MASLD) has emerged as the predominant global etiology of chronic liver disease, with its incidence and prevalence continuously rising amid the obesity epidemic. The human body contains two primary types of adipose tissue: white adipose tissue (WAT) and brown adipose tissue (BAT). The process of adipose tissue browning refers to the phenomenon wherein WAT acquires BAT like characteristics under specific conditions, leading to the generation of beige adipocyte clusters within WAT. This process is critically linked to metabolic diseases such as MASLD. Peroxisome proliferator activated receptors (PPARs) constitute a class of nuclear receptor proteins that function as transcription factors to regulate gene expression. PPARs play pivotal roles in adipose tissue biology, particularly in the process termed adipose tissue browning. These functions of PPARs have garnered significant attention due to their potential as therapeutic targets for MASLD and metabolic syndromes, including obesity, diabetes, and dyslipidemia. PPARs may exert therapeutic effects on MASLD by promoting white adipose tissue browning; however, this mechanism lacks robust clinical evidence, and the safety profile of PPAR agonists requires further comprehensive evaluation.